2021
DOI: 10.14639/0392-100x-n1081
|View full text |Cite
|
Sign up to set email alerts
|

Hashimoto’s thyroiditis in papillary thyroid carcinoma: a 22-year study

Abstract: Objective. We retrospectively investigated whether there is a relationship between Hashimoto's thyroiditis (HT) and papillary thyroid carcinoma and studied the effect of HT on prognostic factors. Methods. 1080 patients, who underwent thyroidectomy in our hospital and received a diagnosis of papillary thyroid carcinoma, were included in the study. In histopathological specimens, the diagnosis of papillary thyroid carcinoma was reconfirmed and non-neoplastic areas in the same specimen were evaluated in terms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 20 publications
2
11
0
Order By: Relevance
“…In recent years, the incidence of PTC with HT is increasing [1,2,3] . An epidemiological study reported that PTC co-existed with PTC on average about 23% [9] , and in this study, this value was higher. The exact relationship between them has not been elucidated, but some studies have suggested that they have same immune link and same gene expression, and patients with HT have a higher risk of PTC [6,7,10,11] .Ultrasonography is one of the most important methods to diagnose thyroid diseases at present, including conventional two-dimensional ultrasound, Doppler ultrasound, shear wave elastography, superb micro-vascular imaging and contrast-enhanced ultrasound.…”
Section: Discussionsupporting
confidence: 42%
“…In recent years, the incidence of PTC with HT is increasing [1,2,3] . An epidemiological study reported that PTC co-existed with PTC on average about 23% [9] , and in this study, this value was higher. The exact relationship between them has not been elucidated, but some studies have suggested that they have same immune link and same gene expression, and patients with HT have a higher risk of PTC [6,7,10,11] .Ultrasonography is one of the most important methods to diagnose thyroid diseases at present, including conventional two-dimensional ultrasound, Doppler ultrasound, shear wave elastography, superb micro-vascular imaging and contrast-enhanced ultrasound.…”
Section: Discussionsupporting
confidence: 42%
“…They also warn against unnecessary lymph node dissections [38]. Hanege et al found an increased incidence of multifocality in HT patients and therefore suggest surgical intervention that considers this risk [21].…”
Section: Protective Effects Of Hashimoto's Thyroiditis On Papillary T...mentioning
confidence: 99%
“…In the subgroup of patients with HT, the NAFLD group had a significantly higher incidence of multifocal lesions than the non-NAFLD group. Several studies have verified that patients with HT, who develop PTC, have an increased risk of having multifocal tumors [ 28 , 29 ]. Our results suggested that the occurrence of NAFLD and HT together increases the incidence of multifocal tumors; however, further studies are required to confirm this pattern.…”
Section: Discussionmentioning
confidence: 99%